OS X App Development with CloudKit and Swift - Wade, Bruce (Apress : Imprint: Apress, 2016)
This book is your step-by-step guide to learning OS X app development using CloudKit and Swift. All the development will be done using Apple's Swift 2 programming language. You'll see how to define data for your app and build a prototype with Sketch 3 and Keynote. Using CloudKit to store OS X application data, and separate public and private data, readers will learn how to control which data can or cannot be changed in a public data store. OS X App Development with CloudKit and Swift takes you from prototyping your app with Sketch 3 all the way through building a data-driven app using CloudKit, and everything in between. OS X App Development with CloudKit and Swift will show you how to: Create Test Data with CloudKit Dashboard Refine a prototype Update CloudKit Data from an app Add Local Cache to improve performance Add OS X App Development with CloudKit and Swift.